The coder's path to wealth and independence - Beckner, Mark (Apress, 2014)
Developers, programmers, technical architects, and consultants: You are highly skilled and have deep commitment to your craft as well as the motivation to excel. It's time to step away from the perceived security of a full-time salaried position, or a marginally successful solo business, and step into a world of freedom, independence, and wealth. With your current technical skills, and an open mind, you can rapidly build a highly successful and ethical business-and on your own terms. The Coder's Path to Wealth and Independence explains how. Mark Beckner, himself, a highly successful itinerant developer, shows you how to transform yourself from a skilled programmer into a highly creative and effective businessperson leveraging the skills you already have. You will learn to create opportunities where none have existed, create value for yourself and those you work with, substantially increase your income, define your ideals, and realize your dreams. By utilizing the unique strategies outlined in The Coder's Path to Wealth and Independence to build your practice, you will find your path to personal, professional, and financial prosperity. The Coder's Path to Wealth and Independence will show you how to: Work from wherever you want Use your technical skills to create a high-revenue, highly independent business Learn the skills of the "rainmaker" to acquire new projects and clients Operate under various fee models, allowing you to increase your wealth and your freedom Rapidly create proposals and contracts Manage projects and execute on your goals with greater skill than ever In short, this book will help you discover a variety of powerful and unique approaches to business that will allow you be highly successful-where, how, and whenever you want.